1/6 because 3 goes into 3 once, and 3 goes into 18 6 times. So the fraction is 1/6
y-y1 = m (x-x1) y+3 = (1/4)(x+4) [using point (x1,y1)] or y–1 = (1/4)(x–12) [using point (x2,y2] [let's use this one since you did] To put this into Standard Form (Ax+By=C), y–1 = (1/4)(x–12) 4y - 4 = x - 12 -x + 4y - 4 = -12 [subtract x from both sides] -x + 4y = -8 [add 4 to both sides] x - 4y = 8 [multiply by (-1) to have x-coefficient positive
Answer:
Estimate: $900.00
Step-by-step explanation:
This cannot be A, B, or C, as it won't make sense with the increase of 75$ each 4 years, with 30K down payment,
Answer:
Bdbebdbeb
Step-by-step explanation:
Bbbsbdb
Answer:
IT is not
Step-by-step explanation:
Let's replace. If it's a solution, it means that BOTH equations has to be true.
![\left \{ {{-10=-5(-24)+22} \atop {-2(-24) +6(-10)=-12} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B-10%3D-5%28-24%29%2B22%7D%20%5Catop%20%7B-2%28-24%29%20%2B6%28-10%29%3D-12%7D%20%5Cright.)
Now, the second equations seems good -
indeed.
First alas isn't. RHS is 142, which is totally not the same as -10.